2015
DOI: 10.1038/bmt.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid chimerism analysis in patients with neurological symptoms after allogeneic cell transplantation

Abstract: Central nervous system (CNS) complications have been described in patients undergoing allogeneic hematopoietic cell transplantation (alloHCT). Cerebrospinal fluid (CSF) analysis is included in the diagnostic workup in patients with neurological symptoms after alloHCT. CSF donor-recipient chimerism analysis usually is not used to evaluate patients with neurological complications after alloHCT. To assess the potential contribution of CSF donor-recipient chimerism in patients with neurological complications, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The presence of donor cells in the CSF after HSCT for ALD has not been reported. Studies on chimerism analysis of CSF following HSCT for patients with hematological malignancies have revealed the presence of donor cells in the CSF 17,18 . In patients with an inherited metabolic disorder, such as metachromatic leukodystrophy and globoid‐cell leukodystrophy, HSCT works through a mechanism that depends on donor cells crossing the blood–brain barrier (BBB) 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of donor cells in the CSF after HSCT for ALD has not been reported. Studies on chimerism analysis of CSF following HSCT for patients with hematological malignancies have revealed the presence of donor cells in the CSF 17,18 . In patients with an inherited metabolic disorder, such as metachromatic leukodystrophy and globoid‐cell leukodystrophy, HSCT works through a mechanism that depends on donor cells crossing the blood–brain barrier (BBB) 19 …”
Section: Discussionmentioning
confidence: 99%
“…Studies on chimerism analysis of CSF following HSCT for patients with hematological malignancies have revealed the presence of donor cells in the CSF. 17,18 In patients with an inherited metabolic disorder, such as metachromatic leukodystrophy and globoid-cell leukodystrophy, HSCT works through a mechanism that depends on donor cells crossing the blood-brain barrier (BBB). 19 ALD reportedly causes BBB dysfunction, as the deficiency of ABCD1 activity results in greater adhesion and transmigration of monocytes across the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Waterhouse et al reported on the utility of CSF STR analysis in adult patients presenting with neurological complications at different time points following allogeneic HSCT. They reported correlation with disease recurrence between STR and flow cytometry results in some cases [3]. Of note, these symptomatic patients had larger numbers of cells present in the cerebrospinal fluid compared to the asymptomatic pediatric patients presented in this paper.…”
Section: Discussionmentioning
confidence: 57%
“…The use of STR loci analysis with polymerase chain reaction in the diagnosis of GVHD after BMT and LT has been well documented . However, this study was primarily done to aid in the detection of a recurrence of underlying malignancy . Here, we describe the use of CSF STR analysis as a tool to aid in the diagnosis of GVHD of the CNS after LT.…”
Section: Discussionmentioning
confidence: 99%